Recent advances on the structure and the function relationships of the TRPV4 ion channel - Raúl Sánchez-Hernández; Miguel Benítez-Angeles; Ana M. Hernández-Vega; Tamara Rosenbaum (Channels, 2024)
The members of the superfamily of Transient Receptor Potential (TRP) ion channels are physiologically important molecules that have been studied for many years and are still being intensively researched. Among the vanilloid TRP subfamily, the TRPV4 ion channel is an interesting protein due to its involvement in several essential physiological processes and in the development of various diseases. As in other proteins, changes in its function that lead to the development of pathological states, have been closely associated with modification of its regulation by different molecules, but also by the appearance of mutations which affect the structure and gating of the channel. In the last few years, some structures for the TRPV4 channel have been solved. Due to the importance of this protein in physiology, here we discuss the recent progress in determining the structure of the TRPV4 channel, which has been achieved in three species of animals (Xenopus tropicalis, Mus musculus, and Homo sapiens), highlighting conserved features as well as key differences among them and emphasizing the binding sites for some ligands that play crucial roles in its regulation.